Prevalencia de hongos en granos de maíz (Zea mays, L.) de Guatemala - Martínez, M.L.; Schieber, E; Gómez Brenes, R; BRESSANI, R. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
The present study was carried out to determine the prevalence of fungi in harvested or stored corn (Zea mays, L.) in Guatemala, and to find out the injury cost on the physical and biological quality of the grain in this country. The results obtained suggest that a high percentage of the harvested corn in the country show considerable contamination by fungi, which are responsible for some of the losses in the field and mainly during storage. The environmental factors and the lack of disease control, are conditions contributing to the high infection of the corn in the plant by the Fusarium moniliforme (91 per cent), this being one of the fungi most commonly identified. The high moisture content of the harvested grain contributes also to a rapid contamination by the storage fungi, Penicillium and Aspergillus. The fungi most frequently identified were: A. versicolor (57. 1 per cent), A. wentii (32. 1 per cent), A. ruber (26.8 per cent), A. echinulatus (25.0 per cent), A. flavus (25.0 per cent) and Cladosporium sp. (26.8 per cent). The fungi that contaminated most of the grain, on the basis of the total samples analyzed, were: Penicillium spp. 44 per cent, Fusarium moniliforme, 31 per cent; A. echinulatus, 10 per cent; y A. versicolor, 7 per cent. The results obtained also indicated that the high moisture content of most of the samples, was higher than that recommended for a safe and optimal storage of the grains, and this was the main factor responsible for the high degree of infections observed. The germination was low in most of the samples with some cases showing 0 per cent germination, depending on the moisture content and the infection. A great variation in the fatty acid content which was related to the moisture content, infection and grain germination was also found.